On some classes of exactly-solvable Klein-Gordon equations - Dutra, Alvaro de Souza [UNESP]; Chen, G. (Elsevier B.V., 2006)
In this work we discuss some exactly solvable Klein-Gordon equations. We basically discuss the existence of classes of potentials with different nonrelativistic limits, but which shares the intermediate effective Schroedinger differential equation. We comment about the possible use of relativistic exact solutions as approximations for nonrelativistic inexact potentials. (c) 2005 Elsevier B.V. All rights reserved.